Kajian Produksi Jamur Kuping (Auricularia Auriculajudae) Pada Berbagai Komposisi Media Tanam - Nugraheni Hadiyanti; Satriya Bayu Aji; Saptorini Saptorini (Kadiri University, 2020)
Ear mushroom (Auricularia aurilajudae) is a potential fungus as a food ingredient and has medicinal properties. Ear mushroom development is profitable because of the high demand and high selling prices. One of the problems in ear mushroom cultivation is the composition of the growing media which has a big effect on its production. This study aims to determine the composition of the best growing media for ear mushroom production. This study used a completely randomized design method (CRD) with one factor, namely the composition of the growing media (1000 gr of sawdust and 200 gr cocopeat (M1); 1000 gr of sawdust and 200 gr of rice bran (M2); 1000 gr of sawdust, 100 gr cocopeat, and 100 gr bran (M3); powder sawdust 1000 gr, cocopeat 135 gr and bran 65 gr (M4); sawdust 1000 gr, cocopeat 65 gr, and rice bran 135 gr (M5). Data were analyzed using analysis of variance and further tests with the least significant difference (LSD) at 5% if the results were significant. The composition of the planting medium had a very significant effect on the number of hoods, cover area, wet weight, and dry weight of ear mushrooms. However, the composition of the planting medium did not affect the growth rate of mycelium. The best composition of the planting medium for ear mushroom production was 1000 gr sawdust, cocopeat 65 gr, and bran 135 gr.Jamur kuping (Auricularia auriculajudae) merupakan jamur potensial sebagai bahan makanan dan berkhasiat obat. Pengembangan jamur kuping menguntungkan karena tingginya permintaan dan harga jual yang tinggi. Permasalahan dalam budidaya jamur kuping salah satunya adalah komposisi media tanam yang berpengaruh besar terhadap produksinya. Penelitian ini bertujuan untuk mengetahui komposisi media tanam yang terbaik bagi produksi jamur kuping. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) dengan satu faktor yaitu komposisi media tanam (serbuk gergaji 1000 gr dan cocopeat 200 gr (M1); serbuk gergaji 1000 gr dan bekatul 200 gr (M2); serbuk gergaji 1000 gr, cocopeat 100 gr dan bekatul 100 gr (M3); serbuk gergaji 1000 gr, cocopeat 135 gr dan bekatul 65 gr (M4); serbuk gergaji 1000 gr, cocopeat 65 gr dan bekatul 135 gr (M5). Data dianalisis menggunakan analisis varian dan uji lanjut Beda Nyata Terkecil (BNT) taraf 5% apabila hasil signifikan. Hasil penelitian menunjukkan bahwa komposisi media tanam berpengaruh sangat nyata terhadap jumlah tudung, luas tudung, berat basah, dan berat kering jamur kuping. Namun komposisi media tanam tidak berpengaruh pada kecepatan laju pertumbuhan miselium. Komposisi media tanam terbaik untuk produksi jamur kuping adalah serbuk gergaji 1000 gr, cocopeat 65 gr dan bekatul 135 gr